PENGARUH PENAMBAHAN TEPUNG Spirulina fusiformis PADA PAKAN TERHADAP TINGKAT KECERAHAN WARNA IKAN KOI (Cyprinus carpio L.) - Desak Made Malini; Tri Dewi K. P; Resty Agustin (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Koi carp (C. carpio L.) is one of ornamental fish which has interesting color. The color of C. carpio L influenced its market price. Quality color of C. carpio L must be increased and it could be increased the market price of C. carpio L. Research aims to determine the effect of Spirulina fusiformis powder addition in diet to enhance color brightness of C. carpio L. The research method used was experimental with one factorial Randomized Complete Design with four treatments and six replicatoins. The concentration of S. fusiformis powder given was 1%, 3%, and 5%. Treatments were given for 28 days and next 28 days without S.fusiformis powder addition. The parameter observed was the color brightness of C. carpio L. The observations used Toca Color Finder (TCF). Data was analyzed statistically by ANOVA. The results showed that addition of S. fusiformis powder in diet influenced brightness color of C. carpio L. Feeding with 1% of S. fusiformis in diet resulted in a brighter color compared to other treatments and control on enhancement color brightness of C. carpio L. Results on TCF showed that level of color brightness of C. carpio L was increased. It can be concluded that adding of S. fusiformis powder in diet can increase brightness color of C. carpio L. Key words: Ciprinus carpio, Color brightness, Spirulina fusiformis.